IISR Keralashree - a high yielding and high quality nutmeg (Myristica fragrans Houtt.) - John Zachariah, B Sasikumar, P A Mathew, B Krishnamoorthy, J Rema, T (Journal of Spices and Aromatic Crops, 2016)
An accession of nutmeg IC-537218 derived from an open pollinated seedling progeny of a high yielding tree from Burliar, Nilgiris, Tamil Nadu, was evaluated under a farmer participatory mode at three locations in two states, Kerala and Tamil Nadu, for yield characters, for 13 years and this accession was found superior for mace and nutmeg yield over the existing variety, IISR Vishwashree, in all the yield parameters studied. The tree is a pure female which flowers profusly and bears oblong shaped yellow fruits. The aril is thick and covers the entire seed and is dark red in colour. The nut is bold and brownish black in colour. The mace and nut of the new variety is rich in sabinene.